2013
DOI: 10.1158/1535-7163.mct-13-0157
|View full text |Cite
|
Sign up to set email alerts
|

Chk1/2 Inhibition Overcomes the Cisplatin Resistance of Head and Neck Cancer Cells Secondary to the Loss of Functional p53

Abstract: Despite the use of multimodality therapy employing cisplatin to treat patients with advanced stage head and neck squamous cell carcinoma (HNSCC), there is an unacceptably high rate of treatment failure. TP53 is the most commonly mutated gene in HNSCC, and the impact of p53 mutation on response to cisplatin treatment is poorly understood. Here we show unambiguously that wild type TP53 (wtp53) is associated with sensitivity of HNSCC cells to cisplatin treatment while mutation or loss of TP53 is associated with c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 47 publications
5
94
0
Order By: Relevance
“…16 Chk1 is an essential kinase in governing cell cycle G 1 /S, S, and G 2 /M phase checkpoints and determining cellular responses to DNA damage. [22][23][24][25][26] In contrast to the well-known utility of Chk1 inhibitors in sensitizing tumors to chemotherapy agents, 23,27,28 Chk1 overexpression or downexpression also occurs in some types of tumors, including breast cancer, ovarian cancer, cervical cancer, and neuroblastoma. 22,[29][30][31][32][33] In our study, we found Chk1 mRNA and protein levels were upregulated in colorectal cancer tissues compared with paired normal tissues, and positively correlated with CCNB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…16 Chk1 is an essential kinase in governing cell cycle G 1 /S, S, and G 2 /M phase checkpoints and determining cellular responses to DNA damage. [22][23][24][25][26] In contrast to the well-known utility of Chk1 inhibitors in sensitizing tumors to chemotherapy agents, 23,27,28 Chk1 overexpression or downexpression also occurs in some types of tumors, including breast cancer, ovarian cancer, cervical cancer, and neuroblastoma. 22,[29][30][31][32][33] In our study, we found Chk1 mRNA and protein levels were upregulated in colorectal cancer tissues compared with paired normal tissues, and positively correlated with CCNB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous inhibition of ERBB2 and NOTCH1 also uncovers a synthetic lethal relationship (59). DNA damage or the presence of unreplicated DNA induces cell cycle arrest in G2/M phase in a manner regulated by CHEK1 in CCC cells overexpressing HNF-1β (60). CHEK1 is reportedly a synthetic lethality partner of ATR, MYC, TP53, WEE1 G2 checkpoint kinase (WEE1), or cyclin-dependent kinase inhibitor 1A (CDKN1A), also known as p21…”
Section: Candidate Mutated Genes For Enhancing the Therapeutic Ratiomentioning
confidence: 99%
“…It has also been reported that the dose strength of genotoxic therapy influences the choice of cellular response pathways in cancer cells. For example, we have shown that supraphysiological dose of cisplatin leads to apoptosis in head and neck squamous cell carcinoma (HNSCC) cells regardless of p53 status; however, a physiological cisplatin dose leads to robust senescence response in wild type p53 HNSCC cells [23]. Advanced malignancies frequently harbor epigenetic silencing, losses, or mutations in the genes critical for TIS pathway induction.…”
Section: Therapy Induced Senescence (Tis)mentioning
confidence: 99%